1994
DOI: 10.1117/12.169940
|View full text |Cite
|
Sign up to set email alerts
|

<title>Interferometric fiber optic gyroscope with inertial navigation performance over extended dynamic environments</title>

Abstract: Litton is developing an interferometric fiber optic gyroscope for future navigation, guidance and stabilization applications. The gyro is presently less than three inches in diameter, which is size competitive with current ring laser gyros ofequal performance. Inthis paper we will report on the bias, scale factor and input axis alignmentperformance of the inertial navigation fiber optic gyroscope over extended, dynamictemperature environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Additionally, application fields which require higher sensitivity(-O.OO1deg/h) exist [24,25], such as space applications and ship navigations. Additionally, application fields which require higher sensitivity(-O.OO1deg/h) exist [24,25], such as space applications and ship navigations.…”
Section: Technologies To Improve the I-fog Sensitivitymentioning
confidence: 99%
“…Additionally, application fields which require higher sensitivity(-O.OO1deg/h) exist [24,25], such as space applications and ship navigations. Additionally, application fields which require higher sensitivity(-O.OO1deg/h) exist [24,25], such as space applications and ship navigations.…”
Section: Technologies To Improve the I-fog Sensitivitymentioning
confidence: 99%
“…For instance, the HOI in IFOG coil inspection and PMF-based sensors will cause misjudgment of the distribution of stress or spliced points. Litton Corporation has pointed out that there are thousands of possible interferences, including HOI, for a single-axis IFOG based on PMF and polarization-maintaining (PM) components [ 11 ]. In the case of distribution sensors, it has been reported that with merely several coupling points there will be many spurious interference signals.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages make FOG devices highly reliable and efficient. It is not unusual to find FOGs as a core element in the implementation of gyrocompasses for navigation instruments [10,11].…”
Section: Introductionmentioning
confidence: 99%